Colorimetric and Naked-Eye Detection of Inorganic Arsenic in Water using BF2-Curcumin and Silica Nanoparticle-BF2-Curcumin Sheets - Farshid Ghorbani; Sheyda Mohammadi Isaabad (آب و فاضلاب)
Accurate and precise measurement of arsenic concentration in water is one of the challenges in areas with the natural potential to create this pollutant. The purpose of this study is to determine the inorganic arsenic concentration by colorimetric and naked eye detection methods. In this regard, the BF2-Curcumin reagent was synthesized and applied. In the first step, this reagent was optimized with consideration of four concentrations: 15, 20, 25 and 30 µM (in 60% ethanol). Then, the three parameters of detection time (1 to 15 min), arsenic concentration (5 to 10000 µg/L) and arsenic pH solution (3 to 10) were investigated in detecting processes. In the second part of the study, the solid phase of reagent was designed and synthesized. For simplicity the arsenic measurement, solid phase consisting of a paper sheet coated with BF2-Curcumin and nano silica was used. The synthesized materials were characterized by FESEM/EDX, XRD, FTIR, VSM, TEM and N2 sorption-desorption analysis. According to the results, during the arsenic detection process, the reagent color changed from orange to blue, and the absorbance intensity decreased at 509 nm, while increasing at 602 nm; 602 nm was selected for detection. The results indicated that the best BF2-Curcumin reagent concentration is 20 µM, with R2=0.97. Under optimum conditions (pH=8 and 3 min), the relationship between absorbance intensity at 602 nm wave length and arsenic ion concentration is between 0.06 and 130 µM, with 0.21 µM as the limit of detection. Investigating the effect of ions interference showed that the concentration (mg/L), cations, and anions that exist in water interfered with arsenic detection. The magnetic adsorbence of Fe3+-TMSPT-MNPs was used to transfer the target analyte and eliminate the interference. On the other hand, the optimum time to produce nano silica sheets was 4 hours. Moreover, there is a good correlation between absorbance intensities at 520 nm and arsenic ion concentration at the 0.06 to 100 µM limitation, with 1.94 µM as the limit of detection in the solid phase. Finally, real samples were collected from the Sirvan River branches in Kurdistan province; then, more than 90 percent were recovered by spiked sample method in the 60 to 80 µM concentration in the both phases. So, this reagent can be employed as a testing kit to detect arsenic in the field.